RIGHT TESTICULAR SEMINOMA IN AN ADULT WITH BILATERAL CRYPTORCHIDISM PRESENTING AS AN ABDOMINAL MASS: A CASE REPORT AND REVIEW OF LITERATURE - Azis, Abdul; Syarif; Mayidah, Maryam; Giffari Makkaraka, Moh. Anfasa; Palinrungi, Muhammad Asykar (Indonesian Urological Association, 2026)
Introduction: Testicular seminomas are relatively rare malignancies that typically present in younger males with normal testicular descent. However, in the context of bilateral cryptorchidism, the presentation and diagnostic challenges are more complex. Objective: This study aims to report a case of a patient with bilateral cryptorchidism with a seminoma originating from the undescended right testis presenting as a rapidly growing abdominal mass. Case(s) Presentation: We reported a 29-year-old man complaining of a mass in the right lower abdomen for the past four months and no palpable testicles. A whole-abdomen computed tomography image revealed an intra-abdominal mass measuring 11 x 10 x 7 cm and suspected malignancy originating from the undescended testicles. Discussion: The patient underwent a right orchidectomy and a left orchidopexy. Histopathology confirmed seminoma of the specimen with pT1N0M0 staging. The patient was discharged and later referred to the oncology department. Conclusion: This case emphasizes the importance of promptly genitourinary evaluation during a regular physical examination and closely monitoring individuals with undescended testis due to the potential for it to be a malignancy, especially in patients presenting with an abdominal mass. Keywords: Testicular seminoma, cryptorchidism, case report.